2017
DOI: 10.1016/j.carj.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Managing Incidentalomas Safely: Do Computed Tomography Requisitions Tell Us What We Need to Know?

Abstract: A significant number of requisitions failed to disclose a history of cancer. Without knowledge of prior malignancy, radiologists cannot comply with current guidelines regarding the reporting and management of incidental findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This process poses challenges in certain jurisdictions, where logistical constraints or limited access to previous imaging studies hinder the ability to accurately assess temporal evolution of IPNs. This has been documented in the literature ( 50 ). KOLs noted that in some provinces, all publicly funded imaging is available on a single imaging network, but in other provinces, nearby hospitals use separate imaging networks making comparison with prior imaging cumbersome.…”
Section: Kol Interviewssupporting
confidence: 58%
See 2 more Smart Citations
“…This process poses challenges in certain jurisdictions, where logistical constraints or limited access to previous imaging studies hinder the ability to accurately assess temporal evolution of IPNs. This has been documented in the literature ( 50 ). KOLs noted that in some provinces, all publicly funded imaging is available on a single imaging network, but in other provinces, nearby hospitals use separate imaging networks making comparison with prior imaging cumbersome.…”
Section: Kol Interviewssupporting
confidence: 58%
“…While the KOL interviews were structured to obtain personal clinical experience and opinion, rather than quantitative data, many of the KOL opinions are supported by the literature. For example, the frustration noted by the radiologist KOLs regarding clinical information that is insufficient to allow specific IPN management recommendations mirrors multiple publications documenting poor requisitions as a contributor to medical error ( 50 , 54 - 56 ). Expanded use of electronic medical records may help solve some of the issues regarding missing information on radiology requisitions by automatically populating the missing fields ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risks of radiation exposure and identification of 'incidentalomas' must be weighed against the benefits of early identification of lung cancer. [25][26][27] It is critical to ensure that patients are receiving their age and history appropriate lung cancer screenings as indicated by USPSTF guidelines. At this time, further additional imaging studies to screen for lung cancer clearly not indicated for patients with MF, although further exploration of this topic is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, in comparison with the increased risk development of lung cancer in smokers (SIR 23.4‐302.0) 24 our SIR of 1.89‐8.24 is relatively low. The risks of radiation exposure and identification of ‘incidentalomas’ must be weighed against the benefits of early identification of lung cancer 25‐27 . It is critical to ensure that patients are receiving their age and history appropriate lung cancer screenings as indicated by USPSTF guidelines.…”
Section: Discussionmentioning
confidence: 99%